2014
DOI: 10.1051/0004-6361/201424060
|View full text |Cite
|
Sign up to set email alerts
|

The angular momentum transport by unstable toroidal magnetic fields

Abstract: We demonstrate with a nonlinear magnetohydrodynamic (MHD) code that angular momentum can be transported because of the magnetic instability of toroidal fields under the influence of differential rotation, and that the resulting effective viscosity may be high enough to explain the almost rigid-body rotation observed in radiative stellar cores. We only consider stationary, current-free fields, and only those combinations of rotation rates and magnetic field amplitudes which provide maximal numerical values of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
63
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 20 publications
8
63
1
Order By: Relevance
“…The main candidates invoked so far are internal gravity waves (Charbonnel & Talon 2005;Talon & Charbonnel 2008;Fuller et al 2014) and magnetic fields that either have a fossil origin (e.g., Gough & McIntyre 1998;Spada et al 2010;Maeder & Meynet 2014) or result from magneto-hydrodynamic (MHD) instabilities (e.g. Spruit 1999;Rüdiger et al 2015). However, the relative importance of these processes and the timescales over which they operate is still a matter of active debate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main candidates invoked so far are internal gravity waves (Charbonnel & Talon 2005;Talon & Charbonnel 2008;Fuller et al 2014) and magnetic fields that either have a fossil origin (e.g., Gough & McIntyre 1998;Spada et al 2010;Maeder & Meynet 2014) or result from magneto-hydrodynamic (MHD) instabilities (e.g. Spruit 1999;Rüdiger et al 2015). However, the relative importance of these processes and the timescales over which they operate is still a matter of active debate.…”
Section: Introductionmentioning
confidence: 99%
“…More recently it has been shown that a similar conclusion can be drawn for intermediate-mass stars in the core-He burning phase, where an even milder radial differential rotation was observed, with core-envelope ratios around two . These novel observational constraints prompted new theoretical studies about the efficiency of angular momentum transport caused by internal gravity waves (Fuller et al 2014), MHD instabilities (Rüdiger et al 2015;Jouve et al 2015), or mixed modes themselves (Belkacem et al 2015b,a), but the question remains open.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been used in the context of planetary interiors (Petitdemange et al 2008(Petitdemange et al , 2013 where a modified version of the MRI was shown to be able to operate in the magnetospheric force balance relevant to the Earth's core. In stellar physics, the MRI of a purely poloidal or purely toroidal field was studied using local stability criteria (Menou et al 2004;Masada et al 2006) or using global analysis in spherical (Arlt et al 2003) or cylindrical (Ogilvie & Pringle 1996;Rüdiger et al 2014Rüdiger et al , 2015 geometries, with a particular focus on the induced transport of angular momentum in the last two articles. However, considering the level of differential rotation and the presence of strong magnetic fields in various situations encountered in stellar radiative zones, this mechanism could have attracted more attention.…”
Section: Introductionmentioning
confidence: 99%
“…See Ibáñez-Mejía & Braithwaite (2015) for a discussion of this point. Braithwaite (2006) and Rüdiger et al (2015) find the mechanism in simulations. However, further numerical work is needed.…”
Section: Physical Processes In Radiative Zonesmentioning
confidence: 88%
“…Differential rotation will wind up any seed field into a predominantly toroidal configuration, which is then unstable to an interchange instability (Tayler 1973), and in so decaying, a new poloidal field is produced that can be wound up anew by the differential rotation, thereby closing a dynamo loop (Spruit 2002). This dynamo process should result in transport of angular momentum and chemical elements in the radial direction, and a prescription for this has been implemented in some stellar evolution models (e.g., Heger et al 2005;Suijs et al 2008).…”
Section: Physical Processes In Radiative Zonesmentioning
confidence: 99%